Purification, Characterization, and Substrate Specificity of a Novel Highly Glucose-Tolerant β-Glucosidase fromAspergillus oryzae - Christine Riou; Jean‐Michel Salmon; Marie-José Vallier; Ziya Günata; Pierre Barré (1998)
ABSTRACT Aspergillus oryzae was found to secrete two distinct β-glucosidases when it was grown in liquid culture on various substrates. The major form had a molecular mass of 130 kDa and was highly inhibited by glucose. The minor form, which was induced most effectively on quercetin (3,3′,4′,5,7-pentahydroxyflavone)-rich medium, represented no more than 18% of total β-glucosidase activity but exhibited a high tolerance to glucose inhibition. This highly glucose-tolerant β-glucosidase (designated HGT-BG) was purified to homogeneity by ammonium sulfate precipitation, gel filtration, and anion-exchange chromatography. HGT-BG is a monomeric protein with an apparent molecular mass of 43 kDa and a pI of 4.2 as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and isoelectric focusing polyacrylamide gel electrophoresis, respectively. Using p -nitrophenyl-β- d -glucoside as the substrate, we found that the enzyme was optimally active at 50°C and pH 5.0 and had a specific activity of 1,066 μmol min −1 mg of protein −1 and a K m of 0.55 mM under these conditions. The enzyme is particularly resistant to inhibition by glucose ( K i , 1.36 M) or glucono-δ-lactone ( K i , 12.5 mM), another powerful β-glucosidase inhibitor present in wine. A comparison of the enzyme activities on various glycosidic substrates indicated that HGT-BG is a broad-specificity type of fungal β-glucosidase. It exhibits exoglucanase activity and hydrolyzes (1→3)- and (1→6)-β-glucosidic linkages most effectively. This enzyme was able to release flavor compounds, such as geraniol, nerol, and linalol, from the corresponding monoterpenyl-β- d -glucosides in a grape must (pH 2.9, 90 g of glucose liter −1 ). Other flavor precursors (benzyl- and 2-phenylethyl-β- d -glucosides) and prunin (4′,5,7-trihydroxyflavanone-7-glucoside), which contribute to the bitterness of citrus juices, are also substrates of the enzyme. Thus, this novel β-glucosidase is of great potential interest in wine and fruit juice processing because it releases aromatic compounds from flavorless glucosidic precursors.